PENERAPAN NEURO-LINGUISTIC PROGRAMMING BERBASIS PENDIDIKAN AKHLAK BAGI ANAK SUKU PENESAK PASCA KASUS KONFLIK SOSIAL AGRARIA - Afriantoni, Afriantoni; Rini, Asih Wahyu; Zaini, Herman (MAJU : Indonesian Journal of Community Empowerment, 2024)
The application of NLP Based on Moral Education aims to address the psychological burden on Penesak Tribe children after agrarian social conflicts, which harbor potential emotional outbursts. The Participatory Action Research (PAR) method is used to provide significant benefits to the community and accelerate positive social transformation. This intervention strategy involves motivational training in NLP Based on Moral Education, targeting children as subjects for mental and spiritual recovery. As a result, children affected by social conflicts can practice contemplation techniques, transform themselves, and become important parts of the change process without being trapped in prolonged spiritual mental weakness. They strive to rebuild their region with the moral values embraced by the Ogan Ilir community. The Penesak Tribe children are now able to understand themselves and apply self-control techniques independently, in line with the teachings of NLP Based on Moral Education, which are highly beneficial for their mental and spiritual recovery.